Method for endothermic reaction of solid and method for producing oxide

By laser irradiating limestone or magnesium stone, it enters the fluorescent state, and using internal thermal reaction in the fluorescent state, the problems of impurities and low resource utilization in oxide production in the prior art are solved, and the production of high-purity oxides and efficient utilization of resources are achieved.

JP7649563B2Active Publication Date: 2025-03-21ADACHI SEKKAI INDS
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023026243
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-02-22
Publication Date
2025-03-21
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

The prior art has impurities such as sulfur and ash when producing high-purity oxides, and it is difficult to effectively utilize fine-grained limestone or magnesium, and hydrocarbon emission problems during combustion.

Method used

By laser irradiating limestone or magnesium stone, it enters a fluorescent state, and the oxides in the fluorescent state absorb laser photons for internal heat reaction, and the surrounding solids are heated to high temperatures to achieve the production of high-purity oxides.

Benefits of technology

The production of high-purity oxides is achieved, which reduces hydrocarbon emissions during combustion, improves resource utilization, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649563000001
    Figure 0007649563000001
  • Figure 0007649563000002
    Figure 0007649563000002
  • Figure 0007649563000003
    Figure 0007649563000003
Patent Text Reader

Abstract

To solve the problem that higher purity is required for oxides obtained by firing limestone or the like, and as for production methods, emphases are placed on solving problems related to reduction of carbon dioxide emission for the realization of a decarbonized society.SOLUTION: Provided is a method that includes irradiating, with laser light, an oxide of Ca and / or Mg in a light emitting state involving continuous light emission due to thermal radiation to endothermically react a solid, which is adjacent to the oxide in the light emitting state having absorbed the laser light, by using heat from the oxide in the light emitting state. Also provided is a method of producing the corresponding oxides from carbonates of Ca and / or Mg as the solids.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for endothermic reaction of a solid by heat from an oxide containing Ca and / or Mg in a luminescent state due to thermal radiation, and a method for producing the oxide. [Background technology]

[0002] Oxides obtained from carbonates and hydroxides containing Ca and Mg, such as limestone, dolomite, and magnesite, are used in a wide range of applications that support the core of industrial technology, including steelmaking, cement raw materials, papermaking, building materials, desiccants, fertilizers, and food additives. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-201571 A Summary of the Invention [Problem to be solved by the invention]

[0004] In conventional technology, the oxides can be produced by heating the carbonate in a calcination furnace such as a Mertz furnace. However, the oxides produced by conventional technology contain impurities such as fuel-derived sulfur and ash, and there has been a demand for oxides of higher purity for use in the above-mentioned industrial and technological applications, for which higher quality has been required in recent years.

[0005] In addition, large equipment such as the Mertz furnace was not suitable for burning fine limestone of 10 mm or less that was surplus at mines, or for producing high-quality quicklime with few impurities.However, if there was a method for burning fine limestone in a short time to produce high-quality quicklime, it was thought that this would be useful in making effective use of limestone resources and meeting various industrial needs.

[0006] Furthermore, in the current effort to realize a decarbonized society, the storage of surplus electricity resulting from the imbalance in the electricity supply and demand balance has attracted attention as an important issue.

[0007] In addition, reducing carbon dioxide emissions has been attracting attention as an important issue in the effort to realize a decarbonized society. Kilns such as the Mertz furnace use fossil fuels such as heavy oil, which results in the emission of large amounts of carbon dioxide. It was thought that not using fossil fuels to kiln limestone would be effective in reducing carbon dioxide emissions.

[0008] Limestone powder granules of 1.0 mm or less that are surplus in mines can only be turned into quicklime of 1.0 mm or less even when fired in a firing furnace, and their uses are limited. For the above industrial and technological uses, not only quicklime of 1.0 mm or less but also granular quicklime of about 10 mm is required. It was thought that if limestone powder granules could be fired into quicklime of about 10 mm in size, it would be possible to make effective use of limestone resources. [Means for solving the problem]

[0009] The present invention includes the following aspects 1 to 9: [Mode 1] A method of irradiating laser light onto an oxide of Ca and / or Mg in a luminescent state that continuously emits light due to thermal radiation, and causing an endothermic reaction in a solid adjacent to the oxide in the luminescent state due to heat from the oxide in the luminescent state that has absorbed the laser light. [Embodiment 2] The method according to embodiment 1, wherein the luminescent oxide is produced due to absorption of laser light. [Embodiment 3] A method for producing the corresponding oxide from the solid Ca and / or Mg carbonate by the method according to embodiment 1 or 2. [Embodiment 4] A method for producing the corresponding oxide from the solid Ca and / or Mg hydroxide by the method according to embodiment 1 or 2. [Embodiment 5] A heat storage medium comprising an oxide produced by the production method according to embodiment 3. [Embodiment 6] An energy storage method using the oxide produced by the production method according to embodiment 4 as a heat storage medium. [Embodiment 7] A method for producing an oxide corresponding to the Ca and / or Mg carbonate, by forming aggregates having a particle size larger than the particle size from the granular Ca and / or Mg carbonate as the solid, using the method according to embodiment 1 or 2. [Embodiment 8] A carbon dioxide absorbent comprising a hydroxide obtained by a hydration reaction of the oxide produced by the production method according to embodiment 3. [Aspect 9] A method for recovering carbon dioxide, characterized in that a hydroxide obtained by a hydration reaction of an oxide produced by the production method according to aspect 3 absorbs carbon dioxide present in its surroundings.

[0010] The solid adjacent to the luminescent oxide may be another solid placed in contact with the luminescent oxide, or may be a solid that was formed as an integral material with the luminescent oxide before it became luminescent, and which constitutes a peripheral region that is in contact with the outer edge of the luminescent oxide formed in part of the integral material. In claim 6, the heat storage medium of the present invention is expressed as a manufacturing method, but this is based on the fact that at the time of filing, it is impossible or almost impractical to directly specify from its structure or characteristics whether the product has been manufactured by the manufacturing method of claim 4. In claim 8, the carbon dioxide absorber of the present invention is expressed as a manufacturing method, but this is based on the fact that at the time of filing, it is impossible or almost impractical to directly specify from its structure or characteristics whether the product has been manufactured by the manufacturing method of claim 3.

[0011] The oxide of Ca and / or Mg is preferably quicklime (CaO), MgO, or a mineral or rock containing CaO·MgO. The Ca and / or Mg carbonate may be preferably a mineral or rock such as limestone (CaCO3), magnesite (MgCO3), or dolomite (CaMg(CO3)2).

[0012] When the oxide of Ca and / or Mg is an oxide of Ca, it is preferable that the luminous quicklime accompanied by continuous emission of light due to thermal radiation is produced due to absorption of laser light by limestone.

[0013] When the Ca and / or Mg oxide is an oxide of Mg, it is preferable that the luminous Mg oxide accompanied by continuous emission of light due to thermal radiation is produced due to absorption of laser light by magnesite.

[0014] When the Ca and / or Mg oxide is an oxide of Ca and Mg, it is preferable that the luminous Ca and Mg oxides accompanying the continuous emission of light due to thermal radiation are produced due to absorption of laser light by dolomite.

[0015] The particle diameter of the granules is preferably 0.1 mm to 1.0 mm, and more preferably 0.3 mm to 0.8 mm.

[0016] As the solid hydroxide of Ca and / or Mg, a substance containing hydrated lime (Ca(OH)2) is also preferred.

[0017] As the solid hydroxide of Ca and / or Mg, a substance containing magnesium hydroxide (Mg(OH)2) is also preferable.

[0018] As the solid hydroxide of Ca and / or Mg, a substance containing dolomite hydroxide (Ca(OH)2·Mg(OH)2) is also preferred. Effect of the Invention

[0019] According to the present invention, a new endothermic reaction accompanied by continuous intense thermoluminescence can be realized.

[0020] According to the present invention, it is possible to provide high purity Ca and / or Mg oxides with a residual CO2 content of 10 mass % or less.

[0021] In addition, it is possible to eliminate impurities such as sulfur and ash (main components are iron, nickel, vanadium, and silica) derived from the fuel during production in advance, and to design a method for producing high-purity Ca and / or Mg oxides.

[0022] According to the present invention, by using limestone as a carbonate of Ca and / or Mg, high-purity quicklime can be produced, and a high-quality raw material can be provided to support basic industries such as steel, cement, and paper.

[0023] According to the present invention, by using magnesite as a carbonate of Ca and / or Mg, oxides can be produced from high-purity fired magnesite, and high-quality raw materials can be provided to support basic industries such as steelmaking.

[0024] According to the present invention, by using dolomite as a carbonate of Ca and / or Mg, oxides can be produced from high-purity calcined dolomite, and a high-quality raw material can be provided to support basic industries such as steelmaking.

[0025] Furthermore, by using the oxide of Ca and / or Mg obtained by the present invention, a high-purity heat storage medium can be obtained, and a high-precision energy storage system can be realized.

[0026] By not using fossil fuels for firing and by using electricity generated from renewable energy sources, carbon dioxide emissions can be significantly reduced.

[0027] According to the present invention, the method for producing a corresponding oxide from a carbonate of Ca can also be applied to a process for endothermic reaction of a carbonate of Ca to a corresponding oxide in cement production.

[0028] By using the hydroxide obtained by the hydration reaction of the Ca and / or Mg oxide obtained according to the present invention, a carbon dioxide recovery system can be realized. [Brief description of the drawings]

[0029] [Figure 1] 1 is a perspective photograph showing the appearance of a bulk-shaped sample formed into a plate shape used in the examples, and shows one formed from limestone as an example. [Diagram 2] FIG. 1A is a diagram showing the configuration of a baking apparatus for performing laser beam baking according to the present invention, and FIG. 1B is a diagram showing the state of a beam formed in a ring mode. [Diagram 3] 1 is a graph showing temperature changes at a portion irradiated with laser light when a limestone sample is continuously irradiated with laser light at a fixed point for 24 seconds. [Figure 4] 1 is a graph modeling the heat input due to irradiance as a function of temperature, using heat flux. [Diagram 5] The temperature measurement results of fixed point irradiation (Figure 3) are reproduced using unsteady heat conduction analysis. [Figure 6] 1 is a photograph showing the intense thermal emission that occurs when a bulk limestone sample is irradiated with laser light. [Figure 7] This is the result of measuring the amount of CO2 remaining in the sample in the area that was baked with the laser beam. The vertical axis represents the laser output, and the horizontal axis represents the laser beam scanning speed. [Figure 8] The following shows the results of observation of the temperature distribution on the limestone surface using an infrared camera under irradiation conditions in which laser light was scanned, with and without strong thermal emission occurring during irradiation. [Figure 9] The XRD results of a sample obtained by firing granular limestone with strong thermal emission by irradiating it with laser light are shown. [Figure 10] The results of Raman spectroscopy of the surface (Figure 10(a)) and cross section (Figure 10(b)) of a limestone sample when it was fired at around 900°C without emitting light, and when it was fired strongly and emitted light are shown. [Figure 11] This figure explains how a sample of bulk limestone is carbon-coated for 5 mm from one end, and laser light is irradiated starting from the coating portion of the sample and scanned toward the opposite side of the sample. [Figure 12] This shows the results of measuring the amount of residual CO2 in the area of ​​a carbon-coated sample that was baked with laser light under the laser output and laser light scanning speed conditions shown in Figure 7. The vertical axis represents the laser output, and the horizontal axis represents the laser light scanning speed. [Figure 13] FIG. 1 is a schematic diagram showing an apparatus for firing a granular sample by irradiating the sample with laser light from above. [Figure 14] FIG. 2 is a schematic diagram of a baking dish for baking a granular sample with laser light. [Figure 15] 1 is a photograph showing the intense thermal emission that occurs when a granular limestone sample is irradiated with laser light. [Figure 16] (a) shows an enlarged image of limestone powder before laser irradiation, (c) shows an enlarged image of quicklime aggregate after firing with continuous strong thermal emission by laser irradiation, and (b) shows an enlarged image of powder that has undergone non-luminescent intermediate firing with no emission during laser irradiation. [Figure 17] 1 is a graph showing temperature changes at a portion of granular slaked lime irradiated with laser light when the laser light is continuously irradiated at a fixed point for 60 seconds. [Figure 18] 1 is a photograph showing an aggregate obtained by subjecting granular slaked lime to laser light firing accompanied by intense thermal emission. [Figure 19] 1 is a graph showing temperature changes at a portion of dolomite irradiated with laser light when the dolomite is placed at a fixed point and irradiated with laser light for 60 seconds. [Figure 20] 1 is a graph showing a state in which, when dolomite is subjected to laser light calcination, continuous strong thermal emission is confirmed, and a residual amount of CO2 of 10 mass % or less is confirmed in the obtained oxide. [Figure 21] 1 is a graph showing temperature changes at a portion of magnesite irradiated with laser light when the magnesite is placed at a fixed point and irradiated with laser light for 350 seconds. [Figure 22] 1 is a graph showing how, when magnesite is subjected to laser beam sintering, continuous strong thermoluminescence is confirmed and the amount of residual CO2 in the resulting oxide is found to be 10 mass % or less. [Figure 23]The XRD results of the oxide of hydrated lime obtained by firing accompanied by strong thermal emission due to laser light irradiation are shown. [Figure 24] The XRD results of dolomite oxide obtained by firing accompanied by strong thermal emission by laser light irradiation are shown. [Diagram 25] 1 shows the XRD result of magnesite oxide obtained by firing accompanied by strong thermal emission due to laser light irradiation. [Figure 26] 1 is a photograph showing an aggregate obtained by subjecting granular dolomite to laser light firing accompanied by intense thermal emission. [Figure 27] 1 is a photograph showing an aggregate obtained by subjecting granular magnesite to laser light firing accompanied by intense thermal emission. EXAMPLES

[0030] Examples of the present invention will be specifically described below, but the present invention is not limited to the description of the following examples. Example 1 (1) Temperature change due to fixed-point laser beam firing In this embodiment, an example in which limestone composed of calcium carbonate is used will be described. The limestone samples used were bulk samples formed into plates of 25 mm × 25 mm × 10 mm, as shown in Figure 1. The limestone sample was attached to the calcination apparatus shown in FIG. 2(a) and calcined using laser light. The laser oscillator is a continuous oscillation single mode fiber laser that can output near infrared light with a wavelength of 1090 nm. The light emitted from the oscillator is transmitted by an optical fiber. An isolator is installed to prevent the oscillator from being damaged by the return light from the sample. An axicon lens and a condenser lens are installed to set the beam shape to ring mode. In order to perform laser light scanning on the limestone sample, the sample fixed to the jig is designed to be moved at any speed by the X, Y, and Z automatic stages. The laser light irradiation and stage scanning are controlled by a trigger using a relay circuit. The size of the beam is set to a size (ring mode with an outer diameter of 2.0 to 3.0 mm and an inner diameter of 1.0 to 1.5 mm) that causes less removal processing than Gaussian mode (laser light irradiation range is solid and approximately circular). By setting the beam shape to ring mode as shown in Figure 2 (b), it becomes easier to control the temperature of the laser light irradiated surface, and it becomes possible to control the burning area and removal processing.

[0031] Figure 3 is a graph showing the temperature change at the laser beam irradiated area when a limestone sample was continuously irradiated with a ring mode laser beam with an outer diameter of 2.0 mm and an inner diameter of 1.0 mm at a fixed point for 24 seconds without scanning at an output of 80 W. The limestone sample used was the bulk limestone sample shown in Figure 1. As shown in Figure 3, when limestone was irradiated with laser beam under certain conditions, the calcination temperature of the limestone sample stagnated at about 1000°C for a certain period of time, and by continuing to irradiate the laser beam, a high temperature of 1900°C was generated along with light emission due to thermal radiation (hereinafter referred to as strong thermal light emission). Note that strong thermal light emission was not confirmed from the limestone sample when the calcination temperature stagnated at about 1000°C (hereinafter referred to as non-luminous intermediate calcination). Considering the mechanism of heat input to the sample when this strong thermal emission occurs, FIG. 4 shows a graph modeled by heat flux with the heat input due to strong thermal emission as a temperature variable. In this model of temperature change of heat flux, a heat flux was applied suddenly from 1000°C, and after reaching 1900°C, the heat flux was suddenly reduced to reproduce strong thermal emission. FIG. 5 shows the result of reproducing the temperature measurement result of FIG. 3 by non-steady heat conduction analysis. It can be seen from FIG. 5 that the temperature stagnation at about 1000°C and the temperature at the time of strong thermal emission can be reproduced. Since the output of the laser light is constant, it is considered that the strong thermal emission can cause a change in the absorptivity of the laser light corresponding to the change in heat flux in the laser light irradiated part, and a new endothermic reaction can be realized. Furthermore, according to the present invention, the generation of strong thermal emission can have a sintering effect due to the new endothermic reaction on the region adjacent to the oxide in the strong thermal emission state, specifically, the solid part of the peripheral region that is in contact with the outer edge of the oxide in the strong thermal emission state and is integral with it, or another solid placed in contact with the oxide in the strong thermal emission state. From the above, it is presumed that when intense thermal emission occurs, not only is there heat input from the irradiated laser light, but also that the absorption rate of the laser light into the sample increases and there is heat input from the intense thermal emission. This is thought to enable the firing temperature of the sample to reach a temperature that is significantly higher than that of conventional firing furnaces. Figure 6 shows the intense thermal emission that occurs when the bulk limestone sample in Figure 1 is irradiated with laser light. When a high-power density laser light is irradiated, light is emitted from the surface irradiated with the laser light.

[0032] Example 2 (1) Firing and residual CO2 measurement using laser light scanning Next, the laser beam was scanned on the limestone sample by driving the automatic stage to search for conditions under which strong thermal emission occurred and did not occur, and the amount of CO2 remaining in the quicklime, which is an oxide corresponding to the burned limestone, was measured in each case. The laser beam scanning conditions were a ring mode laser beam with an outer diameter of 3.0 mm and an inner diameter of 1.5 mm, and the pitch distance was set constant at a distance (3.0 mm) where the beams did not overlap.

[0033] The quicklime from the burned area was extracted by attaching a flat end mill with a blade diameter of 6 mm to a milling machine and scraping off the sample to a depth of 1.0 mm. The amount of residual CO2 in the extracted sample was evaluated by the infrared absorption method specified in JIS R9011. The limestone sample used in this example contained approximately 44% by mass of CO2.

[0034] Figure 7 shows the results of measuring the amount of residual CO2 in the sample in the area that was baked with the laser beam. The vertical axis of Figure 7 is the laser beam output, and the horizontal axis is the scanning speed. In Figure 7, a circle indicates that strong thermal emission was continuously observed during laser beam irradiation, a triangle indicates that strong thermal emission was flickeringly observed, and a cross indicates that strong thermal emission did not occur.

[0035] In addition, the measurement results of the residual CO2 amount are shown in the upper right of each symbol in Figure 7. Under conditions where the strong thermal emission occurs continuously (output 80 W, scanning speed 0.050-0.100 mm / s), the residual CO2 amount was 2.0 mass% or less, and quicklime equivalent to the JIS special designation was obtained. However, when the laser light output was reduced or the scanning speed was increased, the strong thermal emission from the sample shifted to a state where it flickered, and the residual CO2 amount became 15-39 mass%. Then, when the laser light output was further reduced from the condition where the flickering strong thermal emission occurred, or the scanning speed was increased, the strong thermal emission ceased to occur, and the residual CO2 amount rose to 37-41 mass%. Under conditions other than the condition where the strong thermal emission occurs continuously, it was not possible to reduce the residual CO2 amount to 2.0 mass% or less.

[0036] Figure 8 shows the results of observing the temperature distribution on the limestone surface with an infrared camera under the irradiation conditions when the laser beam was scanned, in the cases where strong thermal emission occurred during irradiation and where strong thermal emission did not occur. Regardless of the presence or absence of strong thermal emission, the limestone sample was scanned with the laser beam under the same conditions (output 80 W, outer diameter 3.0 mm, inner diameter 1.5 mm). From Figure 8, when strong thermal emission did not occur, the maximum temperature was about 1000°C (corresponding to the cross mark in Figure 7) (the right side of Figure 8 shows only the white area of ​​about 1000°C), whereas when strong thermal emission occurred, the maximum temperature rose to about 1800°C (corresponding to the circle mark in Figure 7) (the black central part of the left side of Figure 8 shows about 1800°C). Conventionally, quicklime is produced by calcining limestone, by heating to 900°C to 1,000°C using a Mertz furnace or the like. As a result, it can be seen that an endothermic reaction occurs in the region between the cross and circle marks in Figure 7, from limestone, which is a carbonate of Ca, to quicklime, which is an oxide of Ca. In addition, the XRD result of the sample that was fired with strong thermal emission by laser light irradiation is shown in Figure 9. According to Figure 9, it was found that quicklime (CaO), which is an oxide of limestone, was produced by firing with strong thermal emission by laser light irradiation. The above-mentioned method for producing quicklime can be explained step by step, comprising a step of irradiating a workpiece containing calcium carbonate with a laser beam, and a step of producing calcium oxide accompanied by continuous light emission due to thermal radiation from the calcium carbonate contained in the workpiece by an endothermic reaction caused by the irradiated laser beam.Furthermore, it can be said to be a method for processing calcium carbonate, characterized by having a step of endothermically reacting other calcium carbonate adjacent to the calcium oxide accompanied by continuous light emission by the endothermic reaction from the calcium oxide accompanied by continuous light emission.Furthermore, the method for processing calcium carbonate can be said to be a method for producing quicklime.

[0037] Figure 10 shows the results of Raman spectroscopy of the surface (Figure 10(a)) and cross section (Figure 10(b)) of a limestone sample when it was fired at around 900°C without emitting light, and when it was fired strongly and emitted light. As shown in Fig. 10(a), it was confirmed that the increase in the firing width on the surface was about 2.1% when strong thermal emission was used compared to when it was not. On the other hand, as shown in Fig. 10(b), it was found that the firing depth on the cross section was 0.6 mm when it was not emitted, but increased by 185% to 1.71 mm when strong thermal emission was used. This is thought to be due to the rise in surface temperature caused by the strong thermal emission, resulting in a large increase in firing depth. This is thought to have produced a unique firing effect in which heat was applied from the area where strong thermal emission was generated to the adjacent surrounding area, providing a firing method other than laser light, thereby realizing high-temperature firing that could not be achieved by firing in conventional firing furnaces.

[0038] Furthermore, looking at Figure 10(b), in the case of non-luminous intermediate baking, a constant baking depth was observed, but when strong thermal emission occurred, a semi-elliptical baking area was observed centered on the laser light scanning line. When strong thermal emission did not occur, only heat input from the laser light formed a relatively low temperature distribution at the center of the ring, whereas when strong thermal emission occurred, the heat input from strong thermal emission was also added, making the temperature at the center of the ring higher, resulting in a semi-elliptical baking area. Therefore, it was found that the temperature distribution is significantly different when strong thermal emission occurs and when it does not, and that by controlling this, baking that avoids localized heat input can be achieved by taking advantage of the characteristics of the ring mode. However, the shape of the beam that can be used in the present invention is not limited to the ring mode, and the present invention can also be implemented with Gaussian mode or other shapes. From the above, it became clear that the use of laser light irradiation accompanied by strong thermal emission in firing reduces the amount of residual CO2 and increases the firing width and firing depth, making a significant contribution to firing.

[0039] Furthermore, quicklime is produced by pyrolyzing limestone through burning, and industrially, the lower the residual CO2 content, the higher the grade; JIS R9001 specifies that a content of 2.0 mass% or less is considered special. Furthermore, the special quicklime can be used for steelmaking. By using high-quality quicklime as a basic flux to remove impurities such as sulfur and phosphorus from the main raw materials such as molten iron and scrap iron, it becomes possible to produce high-quality steel.

[0040] By utilizing the heat input from intense thermal luminescence, it has become possible to calcine quicklime that meets the JIS special standard. Furthermore, according to the present invention, impurities such as fuel-derived sulfur and ash (main components are iron, nickel, vanadium, and silica) are not mixed into the product Ca and / or Mg oxides, and a high-purity oxide product can be provided, making this a calcination method that is also environmentally advantageous.

[0041] Example 3 The bulk limestone sample was carbon-coated from the edge by 5 mm using a blackbody spray THI-1B (manufactured by Tasco Japan Co., Ltd.) (hereinafter referred to as the coated sample). The laser beam, which was in the same ring mode as in Example 2, was irradiated from the coating portion of the coating sample, and the sample was fired while scanning toward the opposite side as shown in Figure 11. The results of firing were shown in Figure 12, where the laser output and scanning speed were changed in the same way as in Figure 7. As a result, continuous ionizing luminescence was observed even under some of the conditions where ionizing luminescence flickered in Example 2. When the residual CO2 amount of the sample after firing was measured in the same manner as in Example 2, quicklime with a low residual CO2 amount of 10 mass% or less was obtained, although not all of the samples had a residual CO2 amount of 2.0 mass% or less, as shown in Figure 12. Meanwhile, in this example as well, when ionizing luminescence flickered or no ionizing luminescence occurred, the residual CO2 amount of the sample after firing was more than 10 mass%.

[0042] Moreover, it was possible to promote the intense thermal emission by increasing the absorption rate of the laser light in the limestone sample. It was also confirmed that the intense thermal emission continued continuously even when the laser light was scanned from an area coated with carbon to an area without carbon coating. Therefore, the first important factor in the occurrence of the intense thermal emission is the temperature rise caused by the heat input from the laser light. Furthermore, for the intense thermal emission to continue, it is considered that the temperature rise in the vicinity of the laser light irradiated area caused by the heat input from the laser light and the heat input from the intense thermal emission itself is important.

[0043] Example 4 In addition, by changing the laser light irradiation from above using the device shown in Fig. 13, it is possible to handle granular limestone. In addition, by providing a device for supplying limestone and discharging the burned quicklime, it is possible to configure it so that continuous burning is possible.

[0044] Furthermore, it was found that agglomerates of oxide particles can be formed after firing, which is a unique feature of firing powder or granules accompanied by strong thermal luminescence. An example of this is described in detail below. The samples to be irradiated with the laser beam were limestone particles with particle sizes of 0.3 mm to 0.8 mm. These powder particles were placed in a baking dish as shown in Fig. 14, and in this state, the powder particles were stirred while being vibrated (total amplitude 0.145 mm, vibration speed 54.0 mm / s, vibration frequency 120 Hz) using the laser device shown in Fig. 13, and irradiated with the laser beam.

[0045] As a result, even with limestone powder, we were able to confirm strong thermoluminescence, as shown in Figure 15. Furthermore, Fig. 16 shows an enlarged image of limestone powder before laser irradiation (Fig. 16(a)) and an enlarged image of quicklime aggregate after firing accompanied by continuous strong thermal emission by laser irradiation (Fig. 16(c)). Fig. 16(b) shows an enlarged image of powder that has undergone non-luminous intermediate firing in which no emission is observed during laser irradiation. According to FIG. 16, before the laser beam sintering, the particles were not adhered to each other and were in a state in which they could be freely dispersed on a plane. By carrying out laser beam sintering accompanied by strong thermal emission on such powder or granules, it was possible to obtain aggregates with a particle size of 6 mm to 8 mm in which the particles were adhered to each other. As a result, as an effect unique to the laser beam sintering accompanied by continuous strong thermal emission on powder or granules, it is possible to produce and provide quicklime with a size larger than the raw limestone particles. On the other hand, the particles that were subjected to non-luminous intermediate sintering were in a state in which they could be freely dispersed, just like the particles before the laser beam irradiation, and it was not possible to obtain aggregates.

[0046] Example 5 In this example, a case where slaked lime (Ca(OH)2) was calcined by the method of the present invention will be described. The sample used was a Ca(OH)2 sample made by compressing Ca(OH)2 powder raw material with a manual powder compactor and granulating it into particles with a particle size of about 0.8 mm. A large number of Ca(OH)2 samples were placed in a baking dish and placed in the laser light irradiation device shown in Figure 13. The laser irradiation conditions were a Gaussian mode laser beam with an outer diameter of 2.2 mm, which was irradiated continuously for 60 seconds at a fixed point on the Ca(OH)2 sample without scanning at an output of 80 W. During the laser irradiation, the sample was agitated by applying vibration (total amplitude 0.145 mm, vibration speed 54.0 mm / s, vibration frequency 120 Hz) using a vibrator. The temperature change in the fired area is shown in Figure 17. When Ca(OH)2 was fired with laser light, the temperature also stagnated at around 600°C, after which it rose to around 2000°C accompanied by strong thermoluminescence. This confirmed that continuous strong thermoluminescence was also emitted from Ca(OH)2. Figure 23 shows the XRD results of the oxide of Ca(OH)2 obtained by firing accompanied by strong thermoluminescence when Ca(OH)2 was irradiated with laser light. Figure 23 shows that the oxide (CaO) was produced from Ca(OH)2 by firing accompanied by strong thermoluminescence when irradiated with laser light. Aggregates could also be obtained from Ca(OH)2 powder (circled in Figure 18).

[0047] Example 6 (1) Laser beam sintering of dolomite and magnesite Furthermore, when dolomite and magnesite were subjected to laser beam calcination under the same conditions as in Example 1, the temperature rise stagnated at around 700°C to 900°C, as in the case of limestone, and the temperature rose to around 1900°C by continuing the laser beam irradiation. The temperature rise in the case of dolomite is shown in FIG. 19, and the temperature rise in the case of magnesite is shown in FIG. 21. Continuous ignition was confirmed for 45 seconds or more in dolomite (FIG. 19), and continuous ignition was confirmed for 300 seconds or more in magnesite (FIG. 21). When the amount of CO2 remaining in the oxide in which continuous ignition was confirmed was measured, it was possible to produce an oxide with a high purity of 10% by mass or less, and when the laser beam was irradiated for a longer time, it was possible to produce an oxide with a very high purity of 2.0% by mass or less in all samples (FIGS. 20 and 22). In addition, the XRD result of the dolomite that was burned accompanied by strong thermal emission by laser light irradiation is shown in Figure 24. According to Figure 24, it was found that the oxide (CaO MgO) was generated from the dolomite by burning accompanied by strong thermal emission by laser light irradiation. In addition, the XRD result of the magnesite sintered with strong thermoluminescence by laser irradiation is shown in Figure 25. According to Figure 25, it was found that the oxide (MgO) was generated from the magnesite by sintering with strong thermoluminescence by laser irradiation.

[0048] (2) Formation of aggregates by laser beam sintering of granular dolomite FIG. 26 shows the state of an oxide sample obtained by irradiating 0.4 g of a granular dolomite sample with a particle size of about 0.8 mm, which was in a stirred state using a vibrator (total amplitude 0.145 mm, vibration speed 54.0 mm / s, vibration frequency 120 Hz), with a Gaussian mode laser beam with a beam diameter of 2.2 mm at an output of 80 W for 120 seconds. According to FIG. 26, continuous strong thermal emission was confirmed from the sample irradiated with the laser beam under the above conditions, and aggregates with a diameter larger than the particle size before irradiation were formed (within the circle in FIG. 26). The particle size of the granular dolomite forming the aggregates is preferably 0.1 mm to 1.0 mm, and more preferably 0.3 mm to 0.8 mm.

[0049] (3) Formation of aggregates by laser beam sintering of granular magnesite Fig. 27 shows the state of an oxide sample obtained by irradiating 0.4 g of granular magnesite sample with a particle size of about 0.8 mm, which is in a stirred state by a vibrator (total amplitude 0.054 mm, vibration speed 25.5 mm / s, vibration frequency 120 Hz), with a Gaussian mode laser beam with a beam diameter of 2.2 mm at an output of 80 W for 360 seconds. According to Fig. 27, continuous strong thermal emission was confirmed from the sample irradiated with the laser beam under the above conditions, and aggregates with a diameter larger than the particle size before irradiation were formed (within the circle in Fig. 27). The particle size of the granular magnesite forming the aggregates is preferably 0.1 mm to 1.0 mm, more preferably 0.3 mm to 0.8 mm. In addition, by vibrating the granular sample with a vibrator when forming aggregates in Examples 4 and 6, larger aggregates could be obtained than in the case where no vibration was used. The vibration conditions are not limited to those shown in Examples 4 and 6, and it is sufficient that the sample irradiated with laser light is vibrated when it is in an emission state accompanied by continuous strong thermal emission.

[0050] According to the present invention, it is possible to provide high purity Ca and / or Mg oxides with a residual CO2 content of 10 mass% or less. In addition, impurities such as sulfur and ash (main components are iron, nickel, vanadium, and silica) derived from fuel during production can be preliminarily eliminated, and a method for producing high purity Ca and / or Mg oxides can be designed. Furthermore, by using the Ca and / or Mg oxides obtained by the present invention, a high purity heat storage medium can be obtained, and a high precision energy storage system and a carbon dioxide recovery method can be realized, which is characterized in that the carbon dioxide absorber contains Ca and / or Mg hydroxide obtained by the hydration reaction of the Ca and / or Mg oxides produced by the production method according to the present invention and absorbs carbon dioxide present around the carbon dioxide absorber. In addition, the solid that is subjected to the endothermic reaction according to the present invention can include metals that are the subject of laser processing.

[0051] (Energy storage system) The oxides of Ca and / or Mg obtained by the present invention can be hydrated to generate heat and can be used as a heat source. Furthermore, the hydroxides after the hydration reaction can be irradiated with laser light and fired with strong thermal emission to return them to their oxide form. A highly accurate energy storage system can be constructed using the oxides of Ca and / or Mg as a heat storage medium.

[0052] (CO2 capture method) The carbon dioxide absorber containing the hydroxide of Ca and / or Mg obtained by the hydration reaction of the oxide of Ca and / or Mg can absorb carbon dioxide present in the surroundings. A carbon dioxide recovery method can be realized in which the carbon dioxide absorber having absorbed carbon dioxide is irradiated with laser light and fired with strong heat emission to obtain the oxide and simultaneously extract high-concentration carbon dioxide.

Claims

1. A method for producing a luminescent oxide of Ca and / or Mg that emits light continuously due to thermal radiation, comprising irradiating laser light onto the oxide in the luminescent state with the laser light, and endothermically reacting a carbonate of Ca and / or Mg or a hydroxide of Ca and / or Mg as a solid adjacent to the oxide in the luminescent state with the heat from the oxide in the luminescent state that has absorbed the laser light.

2. 2. The method of claim 1, wherein the luminescent oxide is produced by absorption of laser light.

3. 3. A method for producing the corresponding oxides from the solid Ca and / or Mg carbonates by the method according to claim 1 or 2.

4. 3. A method for producing the corresponding oxides from the solid hydroxides of Ca and / or Mg by the method according to claim 1 or 2.

5. A method for using the oxide produced by the method according to claim 3 as a heat storage medium.

6. 5. An energy storage method using an oxide produced by the production method according to claim 4 as a heat storage medium.

7. 3. A method for producing an oxide corresponding to the Ca and / or Mg carbonate, comprising the steps of: forming aggregates having a particle size larger than the particle size from the solid granular Ca and / or Mg carbonate by the method according to claim 1 or 2.

8. A method for using a hydroxide obtained by the hydration reaction of an oxide produced by the production method according to claim 3 as a carbon dioxide absorbent.

9. A method for recovering carbon dioxide, comprising the step of: absorbing carbon dioxide present in the vicinity of a hydroxide obtained by a hydration reaction of an oxide produced by the production method according to claim 3.

Citation Information

Patent Citations

  • Immobilizing method of carbon dioxide

    JP2012131697A

  • Manufacturing facility for quicklime and manufacturing facility and manufacturing process for slaked lime

    JP2012201571A

  • Chemical heat storage device

    JP2022003304A